2019
DOI: 10.1177/2165079919863082
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Prevention Worksite Wellness Interventions for Health Care Workers: A Narrative Review

Abstract: Background: Health care workers face elevated risk of obesity due to their unique work requirements. The purpose of this systematic review was to present a narrative summary of the characteristics and effectiveness of worksite wellness programs focusing on preventing obesity among health care workers. Method: The databases Medline, CINAHL, Embase, PsycINFO, and PubMed were searched. Experimental and quasi-experimental studies published in English (between 2000 and 2018) that (a) were worksite interventions, (b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 83 publications
(111 reference statements)
2
19
0
Order By: Relevance
“…From the interventions observed, it was possible to deduce that the actions that included several strategies achieved adequate results in the working population. This statement is consistent with the results reported by Upadhyaya et al [71], who concluded that occupational health professionals should continue to be creative in the development of multicomponent interventions (combining behavioral/educational, environmental and organizational support).…”
Section: Discussionsupporting
confidence: 92%
“…From the interventions observed, it was possible to deduce that the actions that included several strategies achieved adequate results in the working population. This statement is consistent with the results reported by Upadhyaya et al [71], who concluded that occupational health professionals should continue to be creative in the development of multicomponent interventions (combining behavioral/educational, environmental and organizational support).…”
Section: Discussionsupporting
confidence: 92%
“…Regulations on food labelling can nudge food companies to reformulate or create healthier food products through nutrient profiling and indirectly through increased consumer demand for marked products [70]. In addition, working with local retail outlets to nudge customers towards healthier options and implementing worksite- [71] or school-based interventions [72] to promote healthy food behaviours have been found to be promising. Stronger government policies and local actions that make food environments more conducive to healthy choices through restricted advertising of unhealthy food and beverages, as well as regulated and user-friendly food labelling, could go a long way in changing the foodscapes in these settings, and ultimately in reducing diet-related NCDs [73][74][75][76][77].…”
Section: Implications For Ncd Prevention and Interventionsmentioning
confidence: 99%
“…Previous reviews of workplace interventions focussing specifically on weight loss found such interventions can produce modest weight loss [ 45 , 46 ]; however, these interventions are often relatively intensive, which may not be appropriate for scale. A recent review of obesity prevention initiatives for health care workers found behavioural interventions delivered by trained professionals via phone, or internet were effective in improving weight-related outcomes [ 47 ]. Such delivery modes could be considered for use in educational settings.…”
Section: Discussionmentioning
confidence: 99%